GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 6424 species occurrences available in GBIF matching the query: TaxonKey: Carcharhinus falciformis (Müller & Henle, 1839) HasCoordinate: true. The dataset includes 6424 records from 45 constituent datasets: 732 records from ecoscope_observation_database. 3 records from CSIRO Ichthyology provider for OZCAM. 14 records from Fishbase. 4 records from Occurrence records of southern African aquatic biodiversity. 2 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 28 records from NCSM Fishes Collection. 7 records from University of Florida Vertebrate Paleontology. 1 records from CUMV Fish Collection (Arctos). 7 records from CSIRO, Soviet Fishery Data, Australia, 1965-1978. 23 records from Museum of Comparative Zoology, Harvard University. 18 records from Ichthyology Collection - Royal Ontario Museum. 2 records from iNaturalist Research-grade Observations. 4029 records from observe_tuna_bycatch_ecoscope. 2 records from CAS Ichthyology (ICH). 5 records from CSIRO, Marine Data Warehouse Biology Records Pre-1998, Australia, 1978-1997. 20 records from Diveboard - Scuba diving citizen science observations. 1 records from Inventario de Peces del SFF Isla Malpelo. 2 records from Northern Territory Museum and Art Gallery provider for OZCAM. 10 records from LACM Vertebrate Collection. 1 records from Western Australian Museum provider for OZCAM. 1 records from Consolidación y sistematización de las colecciones de referencia de peces y mamíferos marinos del ITESM Campus Guaymas. 1 records from Ictiofauna insular del medio y bajo Golfo de California. 1192 records from Elasmobranquios del Golfo de Tehuantepec, litoral chiapaneco. 1 records from Ictiofauna de la Bahía de Banderas Nayarit, Jalisco y zonas adyacentes, México. 1 records from Inventario de la biota marina (invertebrados, peces y macroalgas bentónicos) del parque nacional Isla Isabel. 43 records from NMNH Extant Specimen and Observation Records. 2 records from REVIZEE South Score / Pelagic and Demersal Fish Database (OBIS South America, BRAZIL). 1 records from iziko South African Museum - Fish Collection (AfrOBIS). 114 records from iziko South African Museum - Shark Collection (AfrOBIS). 1 records from CNPE/Coleccion Nacional de Peces. 1 records from IndOBIS, Indian Ocean Node of OBIS. 1 records from Fish Collection of Natural History Museum and Institute, Chiba. 2 records from Colección Nacional de Peces del IBUNAM. 1 records from Queensland Museum provider for OZCAM. 16 records from Bureau of Rural Sciences, Commercial Fisheries Presence, Australia, 2000-2002. 6 records from Geographically tagged INSDC sequences. 1 records from CSIRO, Rachel Cruises, Shark Data, Arafura Sea, North Australia, 1984. 10 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 1 records from ZUEC-PIS - Coleção de Peixes do Museu de Zoologia da UNICAMP. 1 records from European Molecular Biology Laboratory Australian Mirror. 19 records from Listado anotado de los tiburones, rayas y quimeras (Chondrichthyes, Elasmobranchii, Holocephali) de México. 29 records from Australian Museum provider for OZCAM. 1 records from UAIC Ichthyological Collection. 42 records from UF FLMNH Ichthyology. 25 records from The fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences